On the Determinants of Corporate Hedging - NANCE, DEANA R.; SMITH, CLIFFORD W.; SMITHSON, CHARLES W. (Journal of Finance, 1993)
ABSTRACT Finance theory indicates that hedging increases firm value by reducing expected taxes, expected costs of financial distress, or other agency costs. This paper provides evidence on these hypotheses using survey data on firm's use of forwards, futures, swaps, and options combined with COMPUTSTAT data on firm characteristics. Of 169 firms in the sample, 104 firms use hedging instruments in 1986. The data suggest that firms which hedge face more convex tax functions, have less coverage of fixed claims, are larger, have more growth options in their investment opportunity set, and employ fewer hedging substitutes.